The intervention of banana peel smoothies products to lower blood pressure in prehypertensive patients - Dini Nur Khairina; Mira Dewi; Rimbawan Rimbawan (AcTion: Aceh Nutrition Journal, 2025)
The incidence of hypertension in Indonesia is increasing, affecting not only the elderly population but also young adults aged 18–39 years. Prehypertension is an early indicator of hypertension; however, the application of fruit-based interventions remains limited. Bananas, particularly their peels, are abundant in nutrients and bioactive compounds that may mitigate hypertension. This study aimed to assess the impact of banana peel smoothing on blood pressure in individuals with prehypertension. A quasi-experimental pre-post-test design was employed. Thirty-two participants were screened and equally divided into two groups: one receiving banana fruit smoothies, and the other receiving banana peel smoothies. The study was conducted from February to March 2024 at the Faculty of Agriculture, Siliwangi University, Tasikmalaya, West Java. Blood pressure measurements were obtained before and after the intervention, and the data were analyzed using a paired t-test. Both banana fruit and banana peel smoothies significantly reduced blood pressure (p= 0,000) in both interventions. In conclusion, banana peel smoothies exhibited greater efficacy in lowering blood pressure in prehypertensive individuals than banana fruit. Banana peel smoothies represent an effective intervention for reducing blood pressure in prehypertensive individuals, offering a promising and nutrient-rich approach for hypertension management.